Combined effects of oat bran consumption and brisk walking exercise on blood lipid profiles in 40 to 50 years old hypercholesterolemic women - Gaffor, Lily Ana Nooryusra Abdul (Universiti Sains Malaysia, 2016)
Evidences of exercise with moderate intensity can improve body compositions and oat bran containing P-glucan enable to improve lipid profile levels have been reported. However, to date, there was no study on the additional beneficial effects of combined brisk walking and oat bran consumption compared to oat bran consumption alone on blood lipid profiles among hypercholesterolemic women. To investigate the additional beneficial effects of combined oat bran consumption and brisk walking exercise compared to oat bran consumption alone and sedentary without oat bran consumption on blood lipid profiles among hypercholesterolemic women with age ranged from 40 to 50 years old. Thirty three hypercholesterolemic women were randomly assigned into 3 groups: sedentary without oat bran consumption control (C), oat bran consumption alone (Ob) and combined oat bran consumption and brisk walking exercise (ObEx) groups. Pre- and post tests were carried out to measure participants’ body anthropometry, body composition and blood lipid profiles, i.e. serum total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C). During 6 weeks of study period, participants in Ob and ObEx groups consumed 18g of oat bran daily. Participants in ObEx executed brisk walking exercise with intensity of at 55%-70% of the participants’ heart rate maximum for 30 minutes per session, 3 sessions per week for 6 weeks. Participants in ObEx group consumed oat bran 1 hour prior to brisk walking exercise on the exercise days. After 6 weeks of study period, body weight decreased significantly in both Ob (p=0.013)